Dynamic Agricultural Household Bio-Economic Simulator (DAHBSIM) model description - Flichman, Guillermo; Belhouchette, Hatem; Komarek, Adam M.; Drogue, Sophie; Hawkins, James; Chenoune, Roza; Haile, Beliyou; Roberts, Cleophelia; Msangi, Siwa (International Food Policy Research Institute, 2016)
DAHBSIM is a dynamic, bio-economic model of agricultural households that was designed to be applied to a rural, developing country-setting, for the purpose of addressing questions around the biophysical constraints to on-farm agricultural productivity, and the whole-farm implications of alternative strategies to sustainable agricultural intensification. The model links socio-economic and biophysical aspects, in order to better illustrate the environmental and human welfare implications of different agricultural production practices, as they are influenced by policy-driven changes in prices of inputs or outputs, or by changes in the physical environment.